2020
DOI: 10.1163/22134808-20191469
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Emotional Mediation in Explaining Crossmodal Correspondences Involving Musical Stimuli

Abstract: Abstract A wide variety of crossmodal correspondences, defined as the often surprising connections that people appear to experience between simple features, attributes, or dimensions of experience, either physically present or else merely imagined, in different sensory modalities, have been demonstrated in recent years. However, a number of crossmodal correspondences have also been documented between more complex (i.e., multi-component) stimuli, such as, for example, pieces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 111 publications
(166 reference statements)
6
91
0
Order By: Relevance
“…Building on early research by Marks (Marks, 1978 , Marks, 2004 ), that focussed primarily on audiovisual correspondences (see Sathian & Ramachandran, 2020 , for recent reviews and discussion), there has undoubtedly been a widening of research interest in the existence/nature of the crossmodal correspondences that exist between a range of different sensory modalities and stimulus dimensions. There has, for instance been much interest in the correspondences between thermal cues and colours (see Spence, 2020b , for a review) through associations between music and colour/paintings (see Spence, 2020a , for a review), and even colours and basic tastes (see Spence, 2019b ; Spence et al, 2015 , for reviews). Colour-odour correspondences can thus be seen as but one strand of this broadening academic interest in the correspondences that, perhaps unusually, has engaged the interests of both basic researchers and those working in various applied domains (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Building on early research by Marks (Marks, 1978 , Marks, 2004 ), that focussed primarily on audiovisual correspondences (see Sathian & Ramachandran, 2020 , for recent reviews and discussion), there has undoubtedly been a widening of research interest in the existence/nature of the crossmodal correspondences that exist between a range of different sensory modalities and stimulus dimensions. There has, for instance been much interest in the correspondences between thermal cues and colours (see Spence, 2020b , for a review) through associations between music and colour/paintings (see Spence, 2020a , for a review), and even colours and basic tastes (see Spence, 2019b ; Spence et al, 2015 , for reviews). Colour-odour correspondences can thus be seen as but one strand of this broadening academic interest in the correspondences that, perhaps unusually, has engaged the interests of both basic researchers and those working in various applied domains (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research suggested that frequent experience of two different stimulus modality sets (e.g., sweet tastes and round shape) caused crossmodal correspondences (Ernst, 2007;Parise et al, 2014;Spence, 2011). Furthermore, emotion category (e.g., both sweet tastes and round shape are associated with positive emotion) is also associated with crossmodal correspondences (Motoki et al, 2020;Spence, 2019;Velasco et al, 2015). Thus, participants answered questions relating to frequency (i.e., how often they hear/see information pertaining to the relationship between sweet foods and round body shape) and emotion (i.e., how much they associate sweet food/round shape with negative feelings; how much they associate sweet food/round shape with positive feelings, and how much they associate sweet food/round shape with saliency).…”
Section: Questionnairementioning
confidence: 98%
“…We did not measure core affect (valence and arousal), which could improve understanding of putative emotional transfer. For instance, it is not clear whether thermal comfort corresponds to valence (Spence, 2020a). Previous research has shown that warm and cold temperatures are associated with red and blue, respectively (Ho et al, 2014b).…”
Section: Underlying Mechanisms For Taste-temperature Correspondencementioning
confidence: 99%
“…We established our hypotheses based on the emotion mediation hypothesis of cross-modal correspondence. The emotion mediation hypothesis suggests that people associate sensory attributes with other attributes based on similarity in emotional meaning (Spence, 2020a). For example, roundness and sweet taste are well matched because both have a positive valence relative to angularity and other tastes (Velasco et al, 2015).…”
Section: Hypothesesmentioning
confidence: 99%